2006
DOI: 10.2134/jeq2005.0449
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Survival in Manure‐Treated Soils during Simulated Seasonal Temperature Exposure

Abstract: Addition of animal manure to soil can provide opportunity for Salmonella contamination of soil, water, and food. This study examined how exposure of hog manure-treated loamy sand and clay soils to different simulated seasonal temperature sequences influenced the length of Salmonella survival. A six-strain cocktail of Salmonella serovars (Agona, Hadar, Heidelberg, Montevideo, Oranienburg, and Typhimurium) was added to yield 5 log cfu/g directly to about 5 kg of the two soils and moisture adjusted to 60 or 80% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 32 publications
9
62
1
Order By: Relevance
“…However, the difference between the serovars in apparent lettuce colonization might be partially determined by the survival of the different S. enterica serovars in manure-amended soil. S. enterica serovars were found to remain viable for at least several months even though a decline was observed (as expected) (Holley et al, 2006). Especially, in the first weeks after inoculation of S. enterica into the manure prior mixing with soil, no significant difference in survival rate (that is decline in viable cell numbers) between S. enterica serovars is expected.…”
Section: Discussionsupporting
confidence: 62%
“…However, the difference between the serovars in apparent lettuce colonization might be partially determined by the survival of the different S. enterica serovars in manure-amended soil. S. enterica serovars were found to remain viable for at least several months even though a decline was observed (as expected) (Holley et al, 2006). Especially, in the first weeks after inoculation of S. enterica into the manure prior mixing with soil, no significant difference in survival rate (that is decline in viable cell numbers) between S. enterica serovars is expected.…”
Section: Discussionsupporting
confidence: 62%
“…Salmonella bacteria occurred only in the soil at C landfill at 25 MPN g -1 . According to Holley et al (2006), bacilli of Salmonella spp. survival in soil range from 6 to several hundred days, which create a real risk for soil contamination and for the growing plants.…”
Section: Microbiological Parametersmentioning
confidence: 99%
“…Application of manure was also identified as a significant factor that increased the odds of both Salmonella and L. monocytogenes isolation in fields. Numerous studies (37,39,41,(57)(58)(59)(60)(61)(62)(63)(64) have demonstrated that the application of manure to soils can introduce pathogens and may facilitate long-term persistence of pathogens in soil. One study observed Salmonella to persist in manure, manure-amended nonsterilized soil, and manure-amended sterilized soil for 184, 332, and 405 days, respectively (60).…”
Section: Field Practices Associated With Presence Of Pathogensmentioning
confidence: 99%